Narrativas Sobre El Afrontamiento De La Enfermedad, Relaciones Familiares y Red Social De Cuatro Pacientes Oncológicos Con Linfoma de una Fundación en La Ciudad De Bogotá (2015)
In this research some narrative of cancer patients versus coping lymphoma disease, their family relationships and social networks are described, taking into account the beliefs and resources used to deal with cancer. The epistemological basis was social constructionism and qualitative methodology in which it took into account the stories of patients collected through semi-structured interview technique. An interpretative analysis-of narrative of each case, according to the established categories which are coping with the disease, family relationships and social networks took place. The analysis of the interviews allowed the description of meanings key to understanding the phenomenon being studied and the results can extend building used to mobilize resources disease as religious, physical and psychological resources, finding the meaning of life and the redefinition of links family and social system of these patients.